(untitled) (Journal of Information Systems and Technology Management, 2005)
This paper explores the potential impact of collaborative technologies in improving management education. The first goal is to expose students to tools and practices that not only assist them with their current studies, but also serve to reinforce individual and team competencies that can facilitate their entry into the workforce. In their positions as future managers they will be expected to not only be familiar with common business practices but also to understand the implications of information technology for business; in this case with emphasis on tools and techniques that can help businesses flourish in the networked economy. With an ever-increasing recognition that e-learning tools are important for (re-)training employees, these three scenarios offer examples of how business schools might expand the boundaries of e-collaboration to help their students. These experiments have been conducted in management programs. In the first two scenarios, students use collaborative platforms in some of their daily work. The third experiment is based on a student-centred design of a learning portal. Our experience reinforces a certain number of hypotheses influencing the impact of collaborative technologies in management education. To begin with, information systems are often flawed mirrors of the managerial system that they are designed to represent. Secondly, the potential value of collaborative technologies is strongly influenced by organizational contexts, both in and between the university and the business community. Thirdly, the effectiveness of collaborative technologies depends to a large degree upon the depth and coherence of learning objectives fixed for learning and work places. Finally, improving the effectiveness of collaborative technologies requires aligning the design of learning environments with the corporate cultures and visions we are trying to reproduce.